Perkembangan Ilmu Pengetahuan Teknologi dan Jaringan Komunikasi di Nagori Simbolon Tengkoh - Albenopri Simarmata; Jelita Simbolon; Yuri Varanti; Mei Meri Cahayana Damanik; Endang Silalahi; M Fauzi; Roni Agung Hasibuan; Dimas S A Nasution; Dian G Purba (Pusat Riset dan Inovasi Nasional, 2024)
The development of Science and Information and Communication Technology is now increasingly rapid and increasingly widespread down to the village level. The existence of science and technology and ICT can also influence the development of a region, and other benefits. The aim of this research is to identify the development of science and technology and ICT in Nagori Simbolon Tengkoh, both in terms of facilities and infrastructure, as well as human resources. The method used is a descriptive method with the research location in Nagori Simbolon Tengkoh in Simalungun Regency. The results of the analysis from our research show that there are limited human resources who use ICT, but the internet network covers the entire area in Nagori Simbolon Tengkoh.